Oral Health Education Module for Mothers (OHEM) - Mohiuddin, Sidra (Pusat Pengajian Sains Pergigian, 2025)
Oral health is a vital component of overall health and well-being. Establishing good oral hygiene habits early in life can significantly reduce the risk of dental disease and improve oral health outcomes. Recognising the pivotal role mothers play in shaping their children's health behaviours, this Oral Health Education Module for Mothers (OHEM) has been developed as a comprehensive educational tool to empower mothers with the knowledge and skills necessary to instil lifelong oral hygiene practices in their families. OHEM provides essential information on oral health, including the structure and function of teeth, common oral diseases, preventive care strategies, and effective oral hygiene practices. It also outlines structured methodologies for delivering oral health education through lectures, exhibitions, and demonstrations. By equipping mothers with this knowledge, OHEM serves as a bridge between healthcare professionals and families, ensuring that oral health awareness reaches communities in a clear, accessible, and practical manner. The development of OHEM is the result of collaborative efforts by dental public health experts, general dental practitioners, pediatric dentists, and dental nurses from Malaysia and Pakistan. Their expertise and dedication in the review process have resulted in a validated, scientifically sound, and user-friendly manual. OHEM is designed for community-based interventions and mainly benefits families in underprivileged settings with limited access to dental care. However, its principles and practices apply universally to families striving to improve their oral health. We hope OHEM will be a valuable resource for mothers, educators, and healthcare providers. By working together, we can promote a culture of oral health awareness, reduce the burden of dental diseases, and ensure that future generations grow up with strong, healthy smiles.